(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2022)
Afghanistan’s destiny has never appeared to western public opinion so tragically connected to its past experiences as it is today. The collapse of the Afghan regime that safeguarded Western interests has laid bare its various roles: multiplier of dependence, war factory, impunity guarantor, impassable border. But the West doesn’t consist only of institutions and governments: the civil society plays its own role, raises contradictions, and creates opportunities for exchange.